Design Management System for talent.gamehouse.com Modification and Maintainability - Aditya Astono (International Journal of Industrial Research and Applied Engineering, 2018)
Design is not a lasting component within a web application. There will come a time when the design is outdated and requires a new form of styling. However, in order to implement the new design, one or more developers are needed to modify the code of the application. The process will use a considerable amount of resources and time that might be more valuable to use for other more important cases. That is why the idea of creating a Design Management System (DMS) surfaced. DMS is created for talent.gamehouse website so that an individual with no knowledge in web development can alter the styling according to his/her preference. The application will also help developers who work on the website to decrease the time needed to do the design implementation. The process is done through several phases. The first phase is to inject a server-side programming language, such as PHP, Python, and Ruby to the Cascading Style Sheet, which is a presentation document that consists of styling properties for a website. The second phase is to create a database for the styling properties, so that the data is stored in a server instead of the CSS. The last and most crucial phase of the process is to create a function where a styling property can be modified using an SQL query. The query will alter the property to the user’s liking. These phases are all generated through a front-facing site which the users will interact with. The site will be created using Hyper Text Markup Language (HTML), complemented with additional frameworks to enhance the user’s experience. The application was tested through a usability session with one of the stakeholders of the application and generated a positive outcome for the fully-functional end result.